Environmentally safe technology for increasing the durability of hydraulic hammer parts - Tunyk, V. (Харківський національний автомобільно-дорожній університет, 2023)
The object of research is the processes of detonation spraying of important parts of hydraulic hammers with the formation of special structures and properties of surface layers of parts to increase durability in difficult operating conditions. The purpose of the work is to solve the scientific and technological problem of increasing the durability of the working parts of heavy-duty machines based on the use of detonation spraying for contacting surfaces of hydraulic hammer parts. Research method – metallographic, microscopic and X-ray studies, bench tests of the durability of hydraulic hammer parts. In the work, studies on the application of this method were carried out. Test results of parts strengthened by this method are shown , which indicate an increase in the wear resistance of parts by 1.3 times compared to the original version. Structural changes that occur during the test in the surface layers of the parts are characteristic of the phenomena of secondary hardening with a lower level of hardness than on the parts of the previous options.
Екологічно безпечна технологія для підвищення довговічності деталей гідромолота
Keywords: hydraulic hammer; detonation spraying; wear resistance; surface treatment; hardness; durability; 541.124